IMPLEMENTATION OF SUSTAINABLE DEVELOPMENT GOALS ON FOOD SECURITY IN FACING GLOBAL CLIMATE CHANGES: (Descriptive Analysis Study at the Dinas Ketahanan Pangan, Pertanian dan Perikanan Kota Bekasi) - Muhammad Farrel Aryaputra Amri (Universal Institute of Professional Management, 2022)
Food security is one of the global issues outlined in the 2030 Sustainable Development Goals (SDGs) agenda. Namely, ending hunger, achieving food security and better nutrition, and supporting sustainable agriculture. According to the 2018 Food Security Agency, food security is a state condition to provide food for individuals, with sufficient food availability, both in quantity and quality, safe, diverse and diverse. and affordability. We can live healthy, active and productive lives. Food problems are also directly affected by climate and meteorological anomalies that have become increasingly prevalent over the last 10 years. A few decades ago the moon could be a parameter to know the changing seasons, but nowadays it's almost completely changed. The purpose of the study was to determine the implementation of Sustainable Development Goals in Food Security in Facing Global Climates Changes in Bekasi City. This research is a study that explores, discloses, and finds information about the implementation of Sustainable Development Goals in Food Security in Facing Global Climates Changes, so to describe this in this study using field research (field research). Data analysis in qualitative research takes place in cycles and is carried out throughout the research process. Data and information in the form of field notes, interviews with respondents and analysis of documents related to the implementation of the SDGs on food security in the face of global climate change.